The 7 habits of highly ineffective educators - Hercules, Bob.; Lauer, Debbie; Myers, Michael Edgar; Richelieu, Rochelle; Winter, Jim (Jim Conrad).; Wavelength Improvisational Communications Institute; Media Process Group, Inc. (Chicago, IL : Wavelength, Inc., 1999)
Wavelength, an improvisational acting troupe from Chicago, dramatizes seven habits of ineffective educators, in a performance before an audience. Wavelength's goal is to provide a humorous perspective to the issues and challenges within education. Intended for educators.
Show introduction -- Anger management-conflict resolution Habit 1. When in doubt, ream someone out 1st scene: Teacher anger jeopardy -- Community involvement in the classroom Habit 2. So, you think you can do it all yourself 2nd scene: Wide world of teaching -- Multiple intelligence Habit 3. Teach as though all kids learn the same way (Because if they don't, they should 3rd scene: Madrigal -- Multicultural education/diversity Habit 4. Don't tolerate-discriminate 4th scene: Multicultural trends -- Coping with educational changes Habit 5. But we've always done it this way 5th scene: Change therapy -- The opportunity/responsibility of the teacher Habit 6. Evey day get up and say, Hey, there are a lot better things I could be doing with my life 6th scene: Top seven list -- The efficacy of humor Habit 7. Remember, there's nothing funny about education 7th scene: movies for teachers.
Video production, Media Process Group ; musical director, Rick Sladek. ; artistic director, Rochelle Richelieu ; associate director, Debbie Lauer.
Debbie Lauer, Michael Myers, Rochelle Richelieu, Jim Winter and Rick Sladek, piano.
DVD.
No master.
Keywords: Teaching -- Humor; Classroom management -- Humor; Teachers -- Attitudes -- Humor; Discrimination in education -- Humor; Educational innovations -- Humor; Wit and humor in education